Retears and Concomitant Functional Impairments After Rotator Cuff Repair: Shoulder Activity as a Risk Factor. Issue 4 (March 2020) - Chen, Yuzhou; Jiang, Fangyi; Li, Hong; Chen, Shiyi; Qiao, Yang; Li, Yunxia; Hua, Yinghui; Chen, Jiwu; Ge, Yunshen
Background: Most patients return successfully to shoulder involving sports or activity after rotator cuff repairs. It has not been decided yet whether postoperative participation in shoulder activity adds to the risk of retear. Purpose/Hypothesis: The purpose was to verify whether patients who participate in shoulder activities after rotator cuff repair have a higher risk of structural failure than nonactive patients and to investigate the relationship between postoperative shoulder function and tendon integrity in active and nonactive patients. The hypotheses were that (1) active patients have a higher retear rate than nonactive patients and (2) structural failure is associated with worse functional outcomes in active patients. Study Design: Cohort study; Level of evidence, 3. Methods: A cohort study was performed using 145 patients who underwent arthroscopic rotator cuff repair from 2015 to 2017. Functional assessments and magnetic resonance imaging were performed at least 24 months postoperatively. Shoulder activities since 6 months after surgery were rated in 4 categories (sports, job, activities of daily life, and weight of general lifting) as sedentary, light, moderate, or strenuous. The activity level of each patient was defined by the highest rated category. Patients who were involved in light, moderate, and strenuous activity were identified as active for the present study, and the rest were defined as sedentary. The proportion of retears between groups and the functional conditions between retorn and intact tendons were compared. Results: A total of 48 patients were enrolled in the active group, and 97 were enrolled in the sedentary group. The active group demonstrated a significantly higher retear rate than the sedentary group (27.1% vs 11.3%, respectively; P = .016; risk ratio, 2.39 [95% CI, 1.16-4.93]). In the active group, patients with retears showed higher visual analog scale scores for pain, decreased abduction strength, and lower shoulder functional scores (American Shoulder and Elbow Surgeons score, Fudan University Shoulder Score, and Constant-Murley score) than those with healed tendons, whereas in the sedentary group, functional outcomes were generally similar across patients with and without retears. Conclusion: Shoulder activity after the early postoperative period was associated with a high risk of retears in patients who underwent rotator cuff repair. A correlation between inhibited function and structural failure was detected but only in active patients, while sedentary patients with retears retained functional improvements similar to those with intact tendons.